Data Management as a Critical Component of Protecting Corporate Devices - Agassi Melikov; Vagif Gasimov; Samur Ahmadov (Journal of Applied Data Sciences, 2024)
The relevance of the problem under study lies in the growing threat of cyberattacks and unauthorized access to corporate data. The need for effective data management at the moment is due to the increased importance of securing corporate devices, which requires in-depth analysis and understanding of the role of data management in this context. The aim of the study is to comprehensively analyze the role of information governance in securing organizational technology. The used methods were: experiment, systematization, comparison, analysis, synthesis. The main findings of the study emphasize the importance of information management in securing enterprise technology. The study involves the development of a C++ program designed to simulate different scenarios of using data management strategies. This program is designed to demonstrate the effectiveness of different information security techniques in organizational technologies. In addition, a comparative analysis of data control techniques designed to protect organizational devices has been carried out. The results of this analysis are presented in the form of a table that discusses the various aspects of information management in this context. And the developed structural diagram of information management in organizations presents the main components and processes required to secure organizational technology. The paper also provides examples of practical applications of data control techniques in large corporations, emphasizing their importance in protecting sensitive information. This research makes a practical contribution by providing organizations not only with theoretical foundations but also with concrete data governance strategies to enhance the security of corporate devices, which is essential for today’s companies in the face of growing cyber threats. Limitations of the study include biases, simulated situations, and an inability to adequately address issues that arise in the actual world, such as organizational culture and cyber threats.